VARIATION IN SHAFT AND MEDULLARY DIAMETER OF PRIMATE’S HEAD HAIR - CHANDA, SUDESNA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The three major histological components of hair are the shaft, the medulla and the cuticle. These properties have long been utilized to evaluate the nature and significance of personal identification. In human as well as in higher animal sexual dimorphism is an important key for personal identification. The present study attempted to understand the variation of some qualitative variables of hair within different species and between different primates Genus and to identify the sexual dimorphisms within different Species. Since Sexual Dimorphism is one of the major features of evolution sex differences in terms of different histomorphological and quantitative variables might be of basic interest for partial understanding of the evolutionary process. In order to understand that species specific variation and sexual dimorphism, medullary and shaft diameter of human and some non human primates were examined and measured in this present study. Results indicated prominent cases of sexual dimorphism in most of the primate species with regard to their shaft and medullary diameter. On the other hand, significant statistical differences were also noticed between the species with regard to their diameter of shaft and medulla. The obtained results cloud be very useful for the partial understanding of primate evolution on the basis of the quantitative morphological features of primate’s head hair strands.